2003
DOI: 10.1046/j.1523-1755.2003.00044.x
|View full text |Cite
|
Sign up to set email alerts
|

AOPP-induced activation of human neutrophil and monocyte oxidative metabolism: A potential target for N-acetylcysteine treatment in dialysis patients

Abstract: This dual potential of NAC to inhibit phagocyte oxidative responses induced by HSA-AOPP without affecting those mediated by compounds mimicking pathogens supports the proposal of a therapeutic trial with NAC aimed at reducing oxidative stress-related inflammation in hemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
139
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(151 citation statements)
references
References 41 publications
10
139
1
1
Order By: Relevance
“…The in vitro studies have demonstrated that AOPPs are capable of triggering the oxidative burst of human monocyte and neutrophil and stimulating leukocytes to produce more oxidants. [16,26,27] It seems reasonable to assume that oxidative stress in uremia can increase AOPP formation, and that AOPP accumulation may constitute a new molecular basis for enhanced oxidative stress. This positive feedback loop could amplify or maintain the oxidative stress in uremia.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro studies have demonstrated that AOPPs are capable of triggering the oxidative burst of human monocyte and neutrophil and stimulating leukocytes to produce more oxidants. [16,26,27] It seems reasonable to assume that oxidative stress in uremia can increase AOPP formation, and that AOPP accumulation may constitute a new molecular basis for enhanced oxidative stress. This positive feedback loop could amplify or maintain the oxidative stress in uremia.…”
Section: Discussionmentioning
confidence: 99%
“…Before starting the therapy we determined AOPPs (ELISA Marc5+Max, Witko-Sarsat method 7,8 ), albumin cobalt binding (ACB) (COBAS MIRA+, Barr-Or method), glucose (ADVIA 1650, GOD-POD method), creatinine (ADVIA 1650, Jaffe method), urea (ADVIA 1650, enzyme method), ALT (ADVIA 1650, IFCC method), AST (ADVIA 1650, IFCC method), cholesterol (ADVIA 1650, enzyme method), LDL direct (ADVIA 1650, method with direct elimination), HDL (ADVIA 1650, method with direct elimination) and triglycerides (ADVIA 1650, enzyme) values in peripheral venous blood in all individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the observation that proteins are highly susceptible to oxidative stress, there have been few reports of the production of oxidatively modified proteins in HD procedures. Measurement of markers of protein oxidation such as advanced oxidation protein products and carbonyl content have recently been performed to assess oxidative stress under pathological conditions (23)(24)(25)(26). In 2001, Himmelfarb et al (27) reported that the oxidation of albumin accounts for almost all of the excess plasma protein oxidation in uremic patients as demonstrated by SDS-PAGE and an immunoassay using a DNP antibody.…”
Section: Discussionmentioning
confidence: 99%